Igniting Innovation: The Roles of Knowledge Sharing, Transformational Leadership, and Psychological Capital in Driving Innovative Work Behavior - Suyoto; Uswatun Hasanah; Mega Aprillia Pratamasari (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: This research aims to empirically investigate a model that explores the effects of knowledge sharing, psychological capital, and transformational leadership on adopting creative work practices. Methodology: The study involved 162 employees from the hospitality sector in Cilacap, selected from a total population of 255 individuals. Data collection was conducted through an online survey using Google Forms, and the Accidental Sampling method was applied. The data gathered were analyzed using the partial least squares (PLS) technique. Findings: The results reveal that knowledge sharing, psychological capital, and transformational leadership each have a significant and positive impact on employees’ creative work practices. Implications/Novel Contribution: To inspire, foster collaboration, and build trust, management must foster a transformational leadership style. Employees’ psychological capital, including resilience, optimism, hope, and self-confidence, must also be strengthened. If information sharing activities are carried out more successfully, employees tend to use more innovative work methods.